Seasonality of congenital anomalies in Europe. Issue 4 (17th March 2014) - Luteijn, Johannes Michiel; Dolk, Helen; Addor, Marie‐Claude; Arriola, Larraitz; Barisic, Ingeborg; Bianchi, Fabrizio; Calzolari, Elisa; Draper, Elizabeth; Garne, Ester; Gatt, Miriam; Haeusler, Martin; Khoshnood, Babak; et al.
<x xml:space="preserve">Abstract</x> Background This study describes seasonality of congenital anomalies in Europe to provide a baseline against which to assess the impact of specific time varying exposures such as the H1N1 pandemic influenza, and to provide a comprehensive and recent picture of seasonality and its possible relation to etiologic factors. Methods: Data on births conceived in 2000 to 2008 were extracted from 20 European Surveillance for Congenital Anomalies population‐based congenital anomaly registries in 14 European countries. We performed Poisson regression analysis encompassing sine and cosine terms to investigate seasonality of 65, 764 nonchromosomal and 12, 682 chromosomal congenital anomalies covering 3.3 million births. Analysis was performed by estimated month of conception. Analyses were performed for 86 congenital anomaly subgroups, including a combined subgroup of congenital anomalies previously associated with influenza. Results: We detected statistically significant seasonality in prevalence of anomalies previously associated with influenza, but the conception peak was in June (2.4% excess). We also detected seasonality in congenital cataract (April conceptions, 27%), hip dislocation and/or dysplasia (April, 12%), congenital hydronephrosis (July, 12%), urinary defects (July, 5%), and situs inversus (December, 36%), but not for nonchromosomal anomalies combined, chromosomal anomalies combined, or other anomalies analyzed. Conclusion: We have confirmed previously described seasonality for congenital cataract and hip dislocation and/or dysplasia, and found seasonality for congenital hydronephrosis and situs inversus which have not previously been studied. We did not find evidence of seasonality for several anomalies which had previously been found to be seasonal. Influenza does not appear to be an important factor in the seasonality of congenital anomalies. Birth Defects Research (Part A) 100:260–269, 2014. © 2014 Wiley Periodicals, Inc.